Perrault Syndrome Diagnosis in a Patient Presenting to Her Primary Care Provider with Secondary Amenorrhea - Leah May Roberts; Bruce Carnivale (Hindawi Limited, 2019)
Perrault syndrome is a rare autosomal recessive genetic disorder characterized by sensorineural hearing loss and female gonadic eukaryotic dysgenesis. Here, we report the case of a 20-year-old female that presented to her internal medicine physician after suffering from secondary amenorrhea. After multiple negative pregnancy tests done with primary care physicians, a further evaluation by an internal medicine specialist showed an elevated FSH and LH as well as a small uterus and streak ovaries on transabdominal and transvaginal ultrasound. She was referred to the OB-GYN service, gonadal dysgenesis was diagnosed, and proper treatment was initiated. We intend to highlight this presentation of ovarian dysfunction and provide guidance for the proper diagnosis and management of the said disorder.